PROSES PEMBUATAN BUMP STOPER DI SHOCK ABSOEBER MENGGUNAKAN MESIN STAMPING AMADA TORC-PAC BERTEKANAN 35 TON - Gunawan Sari, Dede; Mahmud Yunus, Riza (SEMINAR TEKNOLOGI MAJALENGKA (STIMA), 2023)
When starting to practice at PT. Persada Selaras Indonesia found several problems, one of which is why SPHC-PO material is used in the production of Bump Stopper and what is the production process. Stamping Sheet Metal Press is used in the production process using the Blanking+Draw process and the Triming+pierching process. Based on the process of making a Bump Stopper, this practical work has the goal of knowing the working process of a Stamping Press machine. The methods used in this Job Training are processes by observing, summarizing, and recording data from sources and hard copies from PT. Persada Selaras Indonesia. After carrying out the methods systematically, we get some results from this practical work, including being able to make a product using a Stamping Press machine and knowing the flow of the production process in the automotive part industry. Keywords : Stamping Press, SPHC-PO, Automotive Production Department.